INNV-33. THE IMPACT OF COVID-19 ON NEURO-ONCOLOGY CLINICAL TRIALS DURING WAVE 1 AND WAVE 2 AT A FRONTLINE DETROIT HEALTH CARE SYSTEM. (12th November 2021) - Alton, Joshua; Griffin, Carmen; Wigand, Amanda; Winters, Kenneth; Krozek, Emily; Scarpace, Lisa; Walbert, Tobias; Snyder, James
Abstract: In the wake of the Coronavirus disease outbreak (COVID-19), clinical trial operations were significantly impacted following the shutdown of elective healthcare services and even emergency operations. When the pandemic hit Detroit, Michigan in March 2020, the Hermelin Brain Tumor Center (HBTC) at Henry Ford Health System was consumed in COVID-19 emergency care which affected patient enrollment, conduct of trial activities, therapeutic treatment, deviation from protocol requirements, and sponsor-study site contact. The first Metro-Detroit COVID-19 case was confirmed March 10th 2020. At that time there were 18 active brain tumor clinical trials (phase 1 - phase 3) providing anti-cancer therapies. Trial modifications included decentralized operations to buildings with clinic and radiology access away from inpatient COVID-19 care, utilization of telemedicine for non-essential visits, shipping of investigational products to patient home, and in some cases utilization of local results in place of central histopathological confirmation. By April 2020, trials were ranked based on availability of alternative therapies and subject safety in 4 tiers that correlated with subject benefit and impact on care. Trials were given a prioritization level to commence enrollment with priority given to trials where no standard of care exists. Of the HBTC trials, one was graded Tier 1 and most were graded Tier 2. All patients already enrolled continued on study. As restrictions eased, trials were opened in a sequential manner. Changes that were made during the first wave of the pandemic helped to minimize its effect on clinical trial operation and enrollment during the second wave in Fall 2020. Thus, leading toward a decrease in trial deviations and increased enrollment during the 2nd wave. The changes made during the first wave helped to safely continue enrollment and treatment during the second wave and will have a longstanding impact on how clinical trials will be conducted in the future.